Allergen specific immunotherapy attenuates allergic rhinitis clinical manifestations - S. A. Hashemi Moghaddam; S. A. Mahdaviani; M. Rekabi; G. Shakiba Maram; M. Dolikhani (Медицинская иммунология, 2025)
The prevalence of allergic diseases, including rhinitis and allergic asthma, is increasing in the modern world based on the Hygiene theory. Avoidance of allergens and using drugs to relieve clinical symptoms in these patients are not sufficient and efficient. Currently, allergen-specific immunotherapy is the only stable treatment approach. Previous studies in Iran have investigated the efficiency of this treatment. However, they had not performed a simultaneous follow-up of treatment status, with respect to patients’ recovery and side effects. In the present study, we addressed these issues together. After obtaining informed personal consent, a standard questionnaire form was completed for the selected patients according to the study’s entry conditions. The results were analyzed using SPSS, a statistical software program. Of the 64 patients in the present study with an average age of 34.48 (±10.46) years, 25 were women. Immunotherapy against antigens from trees, grass, weeds, and mites was performed, respectively for 57, 49, 53, and 1 allergy cases in the study, The median (IQR) asthma score in these persons before and after immunotherapy was 8 (5-9) and 2 (1-3), respectively. After immunotherapy, the scores of asthma, wheezing, shortness of breath, and cough in the studied subjects were shown to be significantly decreased (p < 0.0001 for entire group). The median (IQR) score of allergic rhinitis in these people before and after immunotherapy was 16 (12-20) and 2 (1-4), respectively. The scores of allergic rhinitis, sneezing, runny nose, nasal itching, nasal congestion, itchy eyes, watery eyes, and red eyes in these patients were significantly decreased after immunotherapy (p < 0.0001 for the total group). Local, extensive, and systemic complications were reported in 10, 2, and 3 cases, respectively. This study demonstrated that standard immunotherapy using common native allergens can improve significant clinical symptoms in patients with moderate to severe allergic rhinitis and mild-to-moderate allergic asthma who have not responded adequately to conventional therapy. An effective treatment approach should be suggested for these patients.